2019
DOI: 10.1002/gps.5117
|View full text |Cite
|
Sign up to set email alerts
|

SSRI co‐medication with NOAC or VKA does not increase hospitalisation for bleeding: A retrospective nationwide cohort study in Austria 2010‐2015

Abstract: Objectives Non‐vitamin K oral anticoagulants (NOACs) or vitamin K antagonists (VKAs) are used for the prophylaxis and treatment of thromboembolic events. A potential drug–drug interaction and increased bleeding events have been reported with co‐medication of selective serotonin receptor inhibitors (SSRIs) and VKA. The aim of this study was to investigate the bleeding risk of a coprescription of NOAC or VKA with SSRI. Methods Patients with prescription of NOAC or VKA and an antidepressant drug therapy (ADTx) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Moreover, if the coadministration of apixaban and venlafaxine is necessary, it is useful to monitor the patient closely for a possible additive effect on haemostasis 79,89 . On the other hand, an Austrian cohort study indicated that the co‐medication of SSRIs and OACs has no substantial impact on bleeding events, compared with the concomitant administration of OACs with other antidepressants 90 . Other concomitant bleeding‐risk medicines include nonsteroidal anti‐inflammatory drugs (NSAIDs) such as ketoprofen and ibuprofen, having an additive effect on haemostasis 76,91,92 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, if the coadministration of apixaban and venlafaxine is necessary, it is useful to monitor the patient closely for a possible additive effect on haemostasis 79,89 . On the other hand, an Austrian cohort study indicated that the co‐medication of SSRIs and OACs has no substantial impact on bleeding events, compared with the concomitant administration of OACs with other antidepressants 90 . Other concomitant bleeding‐risk medicines include nonsteroidal anti‐inflammatory drugs (NSAIDs) such as ketoprofen and ibuprofen, having an additive effect on haemostasis 76,91,92 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the association of antidepressant use with bleeding risk in OAC users. SSRI use has been associated with an increased risk of bleeding among OAC users in some studies [26,27], but not others [28][29][30]. The findings could potentially be explained by SSRIs' interference with hepatic cytochrome P-450 isoenzyme metabolic pathways, which are responsible for warfarin metabolism [31].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one fifth of eligible study participants included in our analysis were DOAC users. Since few published studies have assessed the risk of bleeding associated with concomitant use of antidepressant and DOAC [ 28 , 30 ], we performed additional stratified analyses and tested for interaction between antidepressant type and OAC type. Results from prior studies showed that SSRI use is not associated with an increased risk of bleeding among AF patients on DOAC [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known regarding the clinical relevance of these drug-drug interactions. Previous studies to explore the effects of antidepressants on bleeding risk in patients taking DOACs also demonstrate conflict results (Sheikh Rezaei et al, 2019;Komen et al, 2020;Marchena et al, 2020). To address this important question, we conducted a nationwide retrospective cohort study to compare the major bleeding risk of patients with AF concurrently treated with DOACs and antidepressants and those who took DOACs alone.…”
Section: Introductionmentioning
confidence: 99%